Multidrug-resistant Neisseria gonorrhoeae infection in heterosexual men with reduced susceptibility to ceftriaxone, first report in Thailand - Naris Kueakulpattana (Nature Portfolio, 2021)
Abstract The global rapid emergence of azithromycin/ceftriaxone resistant Neisseria gonorrhoeae threatens current recommend azithromycin/ceftriaxone dual therapy for gonorrhea to ensure effective treatment. Here, we identified the first two N. gonorrhoeae isolates with decreased ceftriaxone susceptibility in Thailand. Among 134 N. gonorrhoeae isolates collected from Thai Red Cross Anonymous Clinic, Bangkok, two isolates (NG-083 and NG-091) from urethral swab in male heterosexual patients had reduced susceptibility to ceftriaxone (MICs of 0.125 mg/L). Both were multidrug resistant and strong biofilm producers with ceftriaxone tolerance (MBEC > 128 mg/L). NG-083 and NG-091 remained susceptible to azithromycin (MIC of 1 mg/L and 0.5 mg/L, respectively). Reduced susceptibility to ceftriaxone was associated with alterations in PBP2, PBP1, PorB, MtrR, and mtrR promoter region. NG-083 belonged to sequence type (ST) 7235 and NG-091 has new allele number of tbpB with new ST. Molecular docking revealed ceftriaxone weakly occupied the active site of mosaic XXXIV penicillin-binding protein 2 variant in both isolates. Molecular epidemiology results revealed that both isolates display similarities with isolates from UK, USA, and The Netherlands. These first two genetically related gonococcal isolates with decreased ceftriaxone susceptibility heralds the threat of treatment failure in Thailand, and importance of careful surveillance.